Architecture Design Proposal as a Syntax for Elderly Rejuvenation - Grace Novita Silalahi; FX.Teddy Badai Samodra (Jurnal Sains dan Seni ITS, 2018)
Every year there are an additional number of elderly. Old age is the phase of human life cycle where the elderly feel it as the life phase with the longest journey. In this phase elderly mostly feel lost part of themselves and cause depression because elderly feeling lost part of themselves.The elderly as an independent person doesn’t want to depend on their child or their family both physically and economically. Architectural object design for productive elderly that still can fulfil their daily needs and they has desire to work again to spent the rest of their life time for aging productively in a community to work and for life.The proposed architectural object is SOHO (Small Office Home Office) for productive elderly and youth can both learning from each other and working together in one community.Biomimetic from beehive ecosystem level to approach behavior setting syntax for elderly rejuvenation. Beehive ecosystem level inspired how to create a sustainable ecosystem that can lead elderly rejuvenation by using space syntax that suitable with elderly behaviour setting.